A Full-Stokes 3-D Calving Model Applied to a Large Greenlandic Glacier - Todd, J; Christoffersen, P; Zwinger, T; Råback, P; Chauché, N; Benn, D; Luckman, A; Ryan, J; Toberg, N; Slater, D; Hubbard, A (American Geophysical Union (AGU), 2018)
Abstract Iceberg calving accounts for around half of all mass loss from both the Greenland and Antarctic ice sheets. The diverse nature of calving and its complex links to both internal dynamics and climate make it challenging to incorporate into models of glaciers and ice sheets. Here we present results from a new open‐source 3‐D full‐Stokes calving model developed in Elmer/Ice. The calving model implements the crevasse depth criterion, which states that calving occurs when surface and basal crevasses penetrate the full thickness of the glacier. The model also implements a new 3‐D rediscretization approach and a time‐evolution scheme which allow the calving front to evolve realistically through time. We test the model in an application to Store Glacier, one of the largest outlet glaciers in West Greenland, and find that it realistically simulates the seasonal advance and retreat when two principal environmental forcings are applied. These forcings are (1) submarine melting in distributed and concentrated forms and (2) ice mélange buttressing. We find that ice mélange buttressing is primarily responsible for Store Glacier's seasonal advance and retreat. Distributed submarine melting prevents the glacier from forming a permanent floating tongue, while concentrated plume melting has a disproportionately large and potentially destabilizing effect on the calving front position. Our results also highlight the importance of basal topography, which exerts a strong control on calving, explaining why Store Glacier has remained stable during a period when neighboring glaciers have undergone prolonged interannual retreat.